VD_FINDINFO HC / 2021 / 163 vom 10. März 2021 - VD Tribunal cantonal (2021)
DROIT DU TRAVAIL, GRATIFICATION, APPRÉCIATION DES PREUVES, ÉGALITÉ DE TRAITEMENT | 322d CO, 328 CO, 310 CPC (CH), 317 al. 1 CPC (CH)